1998
DOI: 10.1021/la971139z
|View full text |Cite
|
Sign up to set email alerts
|

Highly Stable Si−C Linked Functionalized Monolayers on the Silicon (100) Surface

Abstract: Monolayers that are bonded via a covalent Si−C bond are prepared on a silicon(100) surface by reaction of a 1-alkene with the hydrogen-terminated silicon surface. The monolayers have been analyzed by infrared spectroscopy, X-ray reflectivity, and water contact angle measurements and display a remarkably high thermal stability. The reaction also works well for ω-functionalized 1-alkenes, provided that the functional group is properly protected. After formation of the monolayer, the protecting group can be easil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

54
643
4
4

Year Published

1998
1998
2010
2010

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 508 publications
(705 citation statements)
references
References 46 publications
(84 reference statements)
54
643
4
4
Order By: Relevance
“…31 That is, the silicon-carbon bond is highly stable under a range of conditions. [31][32][33]87 We note that a major departure from the prevailing theories on the hydrosilylation mechanism has recently emerged.…”
Section: Surface Preparationmentioning
confidence: 88%
See 2 more Smart Citations
“…31 That is, the silicon-carbon bond is highly stable under a range of conditions. [31][32][33]87 We note that a major departure from the prevailing theories on the hydrosilylation mechanism has recently emerged.…”
Section: Surface Preparationmentioning
confidence: 88%
“…[23][24][25] As comprehensively reviewed elsewhere, [26][27][28][29][30] and as discussed to an introductory level in a following section of this review (Section 2), formation of molecular layers on crystalline silicon surfaces without an intervening oxide layer is an extremely appealing approach toward robust layers on a surface. [31][32][33][34] Silicon-carbon linked monolayers on silicon substrates are expected to complement and/or extend the applications of the currently most relevant technological material 35 toward the development of atomic scale devices, [36][37][38] diverse molecular devices, [39][40][41][42][43][44][45][46][47][48] and well-defined sensing interfaces. [49][50][51][52][53] The following sections are intended as an up-to-date presentation of the topic of molecular layers on non-oxidized silicon surfaces.…”
Section: Jason B Harpermentioning
confidence: 99%
See 1 more Smart Citation
“…They also have the advantage of direct compatibility with organic materials via the strong and stable Si-C bond, providing a larger degree of freedom and flexibility in possible surface passivations and functionalities. [3][4][5][6][7][40][41][42][43] For example, it was recently demonstrated that H-passivated Si-np can be directly functionalized through a Si-C linkage terminating with a carboxylic acid group toward the solvent. This modification preserves the strong PL of the Si core, adds a hydrophilic interface for stability in aqueous media, and is easily reacted with primary amines to label biomolecules, all while adding only a small amount to the overall size.…”
Section: Introductionmentioning
confidence: 99%
“…The analysis has generally focused on the source of PL and the debate between the quantum confinement (delocalized) and surface state (localized) mechanisms. Researchers studying porous Si structures, [40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57] for example, have attributed the PL to various sources ranging from quantum-confined nanorods and nanodots [44][45][46] to surface state silanone and siloxane groups. [47][48][49][50][51][52][53][54][55][56] For Si and Ge nanoparticles prepared through various routes such as solution-phase synthesis, [1][2][3][4][8][9] electrochemical etching, 10-13 laser ablation, 14,15 and using supercritical fluids, [16][17][18] the suggested PL sources have ranged from delocalized quantum confinement states 15 to localized SiSi surface dimer states.…”
Section: Introductionmentioning
confidence: 99%